Measurements of the Dielectric Properties of Wet Snow Using a Microwave Technique. - Sweeny,Bruce D.; Colbeck,Samuel C. (1974)
An accurate method of measuring liquid water in snow covers is required to determine the properties of wet snow. The dielectric properties of wet snow must be utilized to adequately measure its liquid water content. In this study the effect of liquid water on the complex dielectric constant of natural snow is determined in the microwave frequency range. Deloor's method for calculating the dielectric constant for mixtures and the results of waveguide experiments on samples of wet snow and glass beads are used to construct a calibration curve relating the measured dielectric loss factor directly to the water content of wet snow. The results are independent of porosity, past history and chemical impurities. A relation between the effective dielectric constant and the porosity and water content is proposed and tested experimentally. The general nature of this relation is described and suggestions are made for the development of a more precise relation. It is concluded that the dielectric constant is a function of porosity and water content only.